Catalytic Carbon–Chlorine Bond Activation by Selenium‐Based Chalcogen Bond Donors. Issue 67 (14th November 2017) - Wonner, Patrick; Vogel, Lukas; Kniep, Florian; Huber, Stefan M.
Abstract: Chalcogen bonding is a noncovalent interaction based on electrophilic chalcogen substituents, which shares many similarities with the more well‐known hydrogen and halogen bonding. Herein, the first application of selenium‐based chalcogen bond donors in organocatalysis is described. Cationic bifunctionalized organoselenium compounds activate the carbon–chlorine bond of 1‐chloroisochroman in a benchmark reaction. While imidazolium‐based derivatives showed no noticeable activation, benzimidazolium backbones yielded potent catalysts. In all cases, syn ‐isomers were markedly more active, presumably due to bidentate coordination, which was confirmed by DFT calculations. Comparison experiments with the corresponding non‐selenated as well as the non‐cationic reference compounds clearly indicate that the catalytic activity can be ascribed to chalcogen bonding. The rate acceleration by the catalyst—compared to the non‐selenated derivative—was about 10 fold. Abstract : The first application of selenium‐based chalcogen bond donors in organocatalysis is described. Cationic bifunctionalized organoselenium compounds activate the carbon–chlorine bond of 1‐chloroisochroman in a benchmark reaction. Several comparison experiments clearly indicate that the catalytic activity can be ascribed to chalcogen bonding.